The true advantage of experience: Anglo-American military leadership on the Pennsylvania frontier from 1750-1765 - Bukowski, Kevin W. (Kansas State University, 2022)
The British and colonial military commanders on the Pennsylvania frontier between 1750 and 1765 developed a successful decentralized command culture independently of similar changes which happened at the same time in Europe. Characteristics of this command culture included: trust, independence, flexibility, focus, and cultural education, a willingness to take responsibility and bias for action among leaders at all levels. The more complex the environment or situation, the more beneficial these characteristics became within a decentralized command culture. In the mid-eighteenth century this culture showed itself in the use of light infantry, disciplined initiative among aggressive offensive minded commanders and subordinates, operational diplomacy, secure offensive bases of operation, and the use of situational expertise to better inform decision making. The implementation of this command culture did not come to the British and colonial leaders without significant frustration and sacrifice before and during the French and Indian War. The foundation lay in the character of the Pennsylvania frontier. The complex nature of the Pennsylvania frontier formed a zone of conflict and cooperation that military leaders, in both peace and war, had to learn to navigate not only just to succeed but just to survive. Early in the period, the French and their Canadian and Indian allies were successful because they were more adept at implementing portions of the new decentralized command culture, though the British and colonials showed Signs of a growing sense of the change that would be needed to defeat their enemies. Leaderson both sides of the battles of Jumonville Glen, Great Meadows, and the Monongahela exhibited the characteristics and showed indicators (or lack thereof) of this new command culture. Responding to Braddock’s defeat, Pennsylvania leaders were forced to seek independent solutions to the catastrophic raids on frontier settlements by the French and Indians. The new British and colonial command culture was fully formed by the time of John Forbes’s capture of Fort Duquesne and the Battle of Bushy Run during Pontiac’s War in 1763.
Keywords: Military leadership; Pennsylvania; Colonial America